Transient juvenile hypoglycemia in GH insensitive Laron syndrome pigs is associated with insulin hypersensitivity - Hinrichs, Arne; Pafili, Kalliopi; Sancar, Gencer; Laane, Laeticia; Zettler, Silja; Torgeman, Malek; Kessler, Barbara; Nono, Judith Leonie; Kunz, Sonja; Rathkolb, Birgit; Barosa, Cristina; Prehn, Cornelia; et al. (Molecular metabolism, 2026)
Background and aims - Fasting hypoglycemia has clinical implications for children with growth hormone (GH)-insensitivity syndrome. This study investigates the pathophysiology of juvenile hypoglycemia in a large animal model for GH receptor (GHR) deficiency (the GHR-KO pig) and elucidates mechanisms underlying the transition to normoglycemia in adulthood. - Methods - Insulin sensitivity was assessed in juvenile and adult GHR-KO pigs and wild-type (WT) controls via hyperinsulinemic-euglycemic clamp (HEC) tests. Glucose turnover was measured using D-[6,6-2H2] glucose and 2H2O. Clinical chemical and targeted metabolomics parameters in blood serum were correlated with qPCR and western blot analyses of liver and adipose tissue. - Results - GHR-KO pigs showed increased insulin sensitivity (p = 0.0019), especially at young age (M-value +34% vs. WT), insignificantly reduced insulin levels, and reduced endogenous glucose production (p = 0.0007), leading to fasting hypoglycemia with depleted liver glycogen, elevated β-hydroxybutyrate, but no increase in NEFA levels. Low hormone-sensitive lipase phosphorylation in adipose tissue suggested impaired lipolysis in young GHR-KO pigs. Metabolomics indicated enhanced fatty acid beta-oxidation and use of glucogenic amino acids, likely serving as compensatory pathways to maintain energy homeostasis. In adulthood, insulin sensitivity remained elevated but less pronounced (M-value +20%), while insulin levels were significantly reduced, enabling normoglycemia and improved NEFA availability. Increased fat mass, but not sex hormones, appeared key to this metabolic transition, as early castration had no effect. - Conclusions - Juvenile hypoglycemia in GH insensitivity results from excessive insulin sensitivity, reduced glucose production, and impaired lipolysis. Normoglycemia in adulthood emerges through increased adiposity and moderated insulin sensitivity, independently of sex hormones. These findings elucidate the age-dependent metabolic adaptations in GH insensitivity.
Online verfügbar: 20. Oktober 2025, Artikelversion: 7. November 2025
Gesehen am 29.01.2026